HMM-based Brazilian Portuguese TTS - Daniela Braga; Pedro, S.; Ribeiro, M.; Henriques, M.; Dias, J. (Proc. Propor 2008 Special Session (Computational Processing of the Portuguese Language)- Applications of Portuguese Speech and Language Technologies, 2008)
In this paper, a Hidden Markov Models-based Text-to-Speech system (hereafter HTS) for Brazilian Portuguese (BP) was presented. The Brazilian Portuguese Text-to-Speech system (hereafter BP TTS), within other languages, will be enabled in several Microsoft products whose release date is still being planning. The architecture of the system was described as well as the main issues arising from this specific language development. The test plan and procedures were presented and its results were discussed. The comprehension tests carried out by 7 listeners gave rise to 98.915% of overall intelligibility rate distributed by the following domains: e-mail/sentences, addresses, person’s names, date and time and news/paragraphs. Another comprehension test was carried out with a competitor commercial system and the obtained overall intelligibility rate was 91.95%.